The Relationship between the Risk Management Practices and Financial Performance of the Nigerian Listed Banks - Oyerogba Ezekiel Oluwagbemiga; Ogungbade Oluyinka Isaiah; Idode Patrick Esiemogie (Journal of Accounting and Management Information Systems (JAMIS), 2016)
We examine the relationship between the risk management practices and financial performance of the listed companies in Nigeria for the period of ten year from 2005 to 2014, with a particular attention on the 21 deposit money banks. Specifically, the study investigates how risk limit setting, risk adherence monitoring, risk policy review, credit risk management, operational risk management and market risk management has impacted the financial performance of listed banks in Nigeria. We employ both the primary (survey questionnaire) and secondary (audited financial statement) as sources of data. The overall results reveals that risk management practices have a statistically significant impact on financial performance. The results also reveals the trend in risk management practices in other developing economy such as Ghana, Pakistan, Kenya, Thailand, Tehran and the current global practices in Serbian and United state as presented in the literature review. This result leads to a recommendation that adequate risk management system should be put in place by the board of directors which should include the establishment of company's annual risk limit, risk appetite and risk strategy to curtail the excessive risk taking of the management. This system should be reviewed regularly to determine its adequacy, effectiveness and compliance level of the management with this risk management system.
Keywords: M41; 650; Risk Management Practices; Market Risk Management; Operational Risk Management; Credit Risk Management; Return on Capital Employed; Earnings per Share.